Late HIV Testing in a Cohort of HIV-Infected Patients in Puerto Rico - Tossas-Milligan, Katherine Y.; Hunter-Mellado, Robert F.; Mayor, Angel M.; Fernández-Santos, Diana M.; Dworkin, Mark S. (Puerto Rico Health Sciences Journal, 2015)
Objective: Late HIV testing (LT), defined as receiving an AIDS diagnosis within a year of one’s first positive HIV test, is associated with higher HIV transmission, lower HAART effectiveness, and worse outcomes. Latinos represent 36% of LT in the US, yet research concerning LT among HIV cases in Puerto Rico is scarce. Methods: Multivariable logistic regression analysis was used to identify factors associated with LT, and a Cochran‒Armitage test was used to determine LT trends in an HIV-infected cohort followed at a clinic in Puerto Rico specialized in the management and treatment of HIV. Results: From 2000 to 2011, 47% of eligible patients were late testers, with lower median CD4 counts (54 vs. 420 cells/mm3) and higher median HIV viral load counts (253,680 vs. 23,700 copies/mL) than non-LT patients. LT prevalence decreased significantly, from 47% in 2000 to 37% in 2011. In a mutually adjusted logistic regression model, males, older age at enrollment and past history of IDU significantly increased LT odds, whereas having a history of amphetamine use decreased LT odds. When the data were stratified by mode of transmission, it became apparent that only the category men who have sex with men (MSM) saw a significant reduction in the proportion of LT, falling from 67% in 2000 to 33% in 2011. Conclusion: These results suggest a gap in early HIV detection in Puerto Rico, a gap that decreased only among MSM. An evaluation of the manner in which current HIV-testing guidelines are implemented on the island is needed.